Psychology of success in football: Case examples from Rugby Union - Hodge, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
This presentation provides an overview of four studies examining various motivational issues related to success in football. Methods Study # 1: Intrinsic and extrinsic motivation amongst professional rugby players. Sample = 25 professional players, 96 amateur players. The questionnaire consisted of the TEOSQ and the SMS; and data analysis employed MANOVA and discrimination function analysis. Study # 2: Achievement goal orientation profiles amongst amateur rugby players. Sample = 297 amateur players. The questionnaire consisted of the TEOSQ and data analysis employed MANOVA and cluster analysis. Study # 3: Training motivation in professional rugby. Sample = five fitness trainers employed in professional rugby. Each trainer participated in an in-depth interview and thematic content analysis was employed. Study # 4: Burnout in elite rugby: Relationships with basic psychological needs fulfillment. Sample = 113 elite rugby players. The questionnaire consisted of the BRSQ, basic needs in sport, and the ABQ. Data analyses employed SEM. Results & Discussion The results from Studies 1 and 2 indicated that intrinsic motivation and relatively high levels of both task and ego goal orientations is the most adaptive goal profile in rugby. Similarly, the results from Study 3 also supported the adaptive influence of intrinsic motivation and task goal orientation with respect to training motivation for professional rugby players. Finally, lower levels of athlete burnout were strongly related to satisfaction of psychological needs (i.e., autonomy, competence, relatedness) and high levels of intrinsic motivation. Conclusion Overall these motivation results demonstrated the adaptive influence of psychological needs satisfaction (i.e., autonomy, competence, relatedness; Self-Determination Theory), intrinsic motivation, and task (achievement) goal orientation with respect to `success` in football.